1988
DOI: 10.1136/adc.63.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Spastic hemiparesis and presumed prenatal embolisation.

Abstract: SUMMARY An infant with clinical evidence of prenatal right subclavian arterial occlusion subsequently developed left hemiparesis with cystic infarction of the territory of the right middle cerebral artery. Perinatal limb but elsewhere they were normal. The arm and forearm circumferences, measured at midpoints, were 1-0 cm smaller on the right than on the left. The rest of the physical examination was unremarkable.Plain radiographs of the cervical spine, chest, and right shoulder were normal. A full blood cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A review of the literature revealed reports of 8 other children who appeared to have had emboli to both an extremity and the brain during the perinatal period [3][4][5][6][7][8][9] (Table 1). Each of these children presented with limb ischemia within 10 minutes of…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A review of the literature revealed reports of 8 other children who appeared to have had emboli to both an extremity and the brain during the perinatal period [3][4][5][6][7][8][9] (Table 1). Each of these children presented with limb ischemia within 10 minutes of…”
Section: Discussionmentioning
confidence: 99%
“…Two had malformation and decreased muscle mass in the affected ischemic limbs, suggesting the occlusion took place in utero. 3,9 Both of the 2 newly presented cases also had abnormal limb appearance at birth.…”
mentioning
confidence: 89%
See 3 more Smart Citations